Prenatal and child vitamin D levels and allergy and asthma in childhood - Sangüesa, Júlia; Sunyer, Jordi; Garcia-Esteban, Raquel; Abellan, Alicia; Esplugues, Ana; Garcia-Aymerich, Judith; Guxens, Mònica; Irizar, Amaia; Júlvez, Jordi; Luque-García, Leire; Rodríguez-Dehli, Ana Cristina; Tardón, Adonina; et al. (Pediatric research, 2023)
Background Early-life vitamin D deficiency may impair immune system development contributing to allergy and asthma onset. Findings from prospective studies are inconsistent. Objective To examine whether maternal and child vitamin D levels are associated with allergic and asthma-related symptoms throughout childhood in a Spanish birth cohort. Methods 25-Hydroxyvitamin D 3 (25(OH)D 3 ) levels were measured in the serum of pregnant women ( N = 2525) and children ( N = 803). Information on allergic and asthma-related symptoms was obtained from repeated questionnaires from 1 to 9 years. Results A total of 19% of mothers and 24% of children had deficient 25(OH)D 3 levels (<20 ng/ml). Higher child 25(OH)D 3 levels at 4 years were associated with lower odds of atopic eczema from 4 to 9 years (adjusted odds ratio = 0.90; 95% CI = 0.84–0.97 per 5 ng/ml). Higher maternal and child 25(OH)D 3 levels were associated with a lower prevalence of late-onset wheezing at the limit of statistical significance (adjusted relative risk ratio (RRR adj ) = 0.86; 95% CI = 0.74–1.00 and RRR adj = 0.76; 95% CI = 0.58–1.02 per 5 ng/ml, respectively). All the remaining associations were null. Conclusion Child 25(OH)D 3 levels at pre-school age are associated with a reduced odds of atopic eczema in later childhood and both maternal and child levels may reduce the prevalence of late-onset wheezing. Impact In this Spanish birth cohort, with a total of 19% of mothers and 24% of children with deficient levels of vitamin D, higher child vitamin D at 4 years of age was associated with reduced odds of atopic eczema up to 9 years. There was also some evidence that higher maternal and child vitamin D levels reduced the prevalence of late-onset wheezing. Although these findings need replication, they may imply optimal vitamin D levels at pre-school age to prevent atopic eczema.